Hubungan Orang Tua-Guru dan Praktik Pengasuhan Ibu pada Keluarga yang Memiliki Anak Berkebutuhan Khusus - Siti Fathonah; Neti Hernawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Mothering practices and support form surrounding environment are needed to stimulate special need children.This research aimed to analyze the correlation of relationships parent-teacher and mothering practices, in familieswith special need children. The research involved mother and teacher of 30 students aged 7-12 years from twoExtraordinary School in West Bogor and South Bogor Sub District, Bogor City. The sample selected usingpurposive method. The result showed that there were positive correlation between the length parent’s educationand the per capita income of the family with the dimensions of maternal consistency. In addition, the parentteacherrelationship had a positive correlation with mother-child relationship at home.The result also found thatthe length of the parent’s education has a positive correlation with the dimension of sharing information.Furthermore, according to the teacher's perception, the mother’s age has a positive correlation with the dimensionof dependability and availability of both parties. But on the contrary, there are negative correlation between thelonger the father’s education with the dimensions of feeling of affiliation and support. And also the children’s agehas a negative correlation with the dimensions of sharing information.